1999
DOI: 10.1046/j.1523-1755.1999.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of transforming growth factor-β in HIV-associated nephropathy

Abstract: Our findings suggest that overproduction of TGF-beta is involved in the pathogenesis of HIVAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 48 publications
(3 reference statements)
1
40
0
2
Order By: Relevance
“…In the kidney, plasmin is known to play a major role in the degradation and turnover of the extracellular matrix and especially the glomerular mesangial matrix. 22 In addition, plasmin has long been hypothesized to be involved in renal stone formation because plasmin and urokinase-type plasminogen activator activities are decreased in stone-forming patients. 23 In that study, van Aswegen and colleagues reported that urate inhibited urokinase/plasmin activities at a pH of 3.9 (in the presence of acetate) but is minimal under alkaline condition (in the absence of acetate).…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, plasmin is known to play a major role in the degradation and turnover of the extracellular matrix and especially the glomerular mesangial matrix. 22 In addition, plasmin has long been hypothesized to be involved in renal stone formation because plasmin and urokinase-type plasminogen activator activities are decreased in stone-forming patients. 23 In that study, van Aswegen and colleagues reported that urate inhibited urokinase/plasmin activities at a pH of 3.9 (in the presence of acetate) but is minimal under alkaline condition (in the absence of acetate).…”
Section: Discussionmentioning
confidence: 99%
“…TMEV-or sham-infected tissue culture supernatants were harvested, 24 hours p.i. We measured TGF-β1 in the supernatants, using an ELISA kit (TGF-β1 Quantikine ® ELISA, R&D System, Inc., Minneapolis, MN) (Wang et al, 2003;Yamamoto et al, 1999).…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…While PAI-1 is essentially undetectable in normal kidney, its mRNA expression and/or protein are increased in numerous models of glomerulosclerosis and in many human glomerular diseases (21)(22)(23)(24)(25)(26)(27), implicating it in the fibrotic process. PAI-1 strongly binds to the vitronectin (Vn) that is laid down at the site of tissue injury (28), concentrating PAI-1 in the fibrotic matrix where it can initially inhibit degradation of the provisional fibrin clot and later inhibit matrix degradation.…”
Section: Introductionmentioning
confidence: 99%